Alcohol abuse in developed and developing countries in the World Mental Health Surveys: Socially defined consequences or psychiatric disorder?. (29th August 2013) - Glantz, Meyer D.; Medina‐Mora, Maria Elena; Petukhova, Maria; Andrade, Laura Helena; Anthony, James C.; de Girolamo, Giovanni; de Graaf, Ron; Degenhardt, Louisa; Demyttenaere, Koen; Florescu, Silvia; Gureje, Oye; Haro, Josep Maria; et al.
<x xml:space="preserve">Abstract</x> Background Previous single country research has raised concerns that: (1) the DSM‐IV diagnosis of alcohol abuse (AA) is met primarily through the hazardous use criterion related to drinking and driving and (2) that the hazardous use and social consequences AA criteria primarily reflect varying socioeconomic and cultural factors rather than psychiatric disorder. Methods Using representative cross‐national data from the 21 countries in the World Mental Health surveys, adults meeting DSM‐IV lifetime criteria for AA but not dependence from 10 developed (n = 46, 071) and 11 developing (n = 49, 761) countries were assessed as meeting AA with the hazardous use or the social consequences criteria. Results Between 29.3% (developed) and 16.2% (developing) of respondents with AA met only the hazardous use criterion. AA cases with and without hazardous use were similar in age‐of‐onset, course, predictors, and psychopathological consequences in both developed and developing countries. Discussion and Conclusions Despite some associations of the AA criteria with socioeconomic factors, the hazardous use and social consequences criteria were significantly associated with psychiatric predictors and sequelae. The findings indicate that these criteria reflect psychiatric disorder and are appropriate for inclusion as DSM‐5 Alcohol Use Disorder criteria. Scientific Significance These findings support a psychiatric rather than a sociocultural view of the hazardous use and social consequences symptoms and provide evidence that they are appropriate diagnostic criteria cross‐nationally with utility in a wide range of socioeconomic environments. This suggests consideration for their adoption by ICD‐11. Further research is needed on the implications of these results for prevention and treatment. (Am J Addict 2014;23:145–155)